Usability of several species for monitoring and reducing the heavy metal pollution threatening the public health in urban environment of Ankara - Bayraktar, Emine Pirinc; Oznur Isinkaralar; Isinkaralar, Kaan (GSC Online Press, 2022)
In the last century, the pollution in the atmosphere significantly increased due to anthropogenic effects including industrial activities and traffic and reached a level threatening human and environmental health. Among these pollution factors, heavy metals that do not easily degrade in nature, tend to bioaccumulate in living organisms, and can be toxic, carcinogenic, and lethal even at low concentrations are among the most important threats in terms of human health. Thus, it is very important to reduce the heavy metal pollution in air, especially in urban areas where the traffic activities that are among the important heavy metal sources are intense. The most effective, affordable, environment-friendly, and sustainable method to be used in monitoring and reducing the heavy metal pollution in air is the use of plants. However, for this purpose, the most suitable species should be determined first. Within the scope of this study, it was aimed to determine the accumulation of Ba, Na, and Ca, which are very common, in the leaves, seeds, and branches of Acer negundo, Aesculus hippocastanum, Tilia platyphyllos, Prunus ceracifera, and Ailanthus altissima that are frequently used in landscaping in urban areas. The results achieved here showed that the concentration of Ba, which is very harmful to human health and compounds of which are toxic, increased with increasing traffic density. It was determined that, among the species examined here, the most effective ones to be used in reducing the Ba concentration were Aesculus hippocastanum and Tilia platyphyllos.
Keywords: Air Pollution; Biomonitor; Heavy metal; Urban Areas; Public Health; 13. Climate action; 11. Sustainability; 15. Life on land; 6. Clean water; 3. Good health; 12. Responsible consumption